IMPLEMENTASI CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN IPA: STUDI OBSERVASI DI SDN GUNGGUNG I - Alviani, Fivi; Kamilah, Mila Kibwatul; Nurhalida, Sitti; Zakinah, Elmi Lailatus; Astuti, Yeni Puji (Universitas Tanjungpura, 2025)
This study aims to describe and analyze the implementation of the Contextual Teaching and Learning (CTL) model in Natural Science (IPA) learning at SDN Gunggung 1. The focus of this study lies in learning strategies, media utilization, and supporting and inhibiting factors in the implementation of CTL. This study uses a descriptive qualitative approach with data collection techniques through direct observation and structured interviews with science teachers. The results of the study indicate that teachers have applied the principles of contextual learning by linking science concepts, such as ecosystems and food chains, to students' real experiences in the school environment. Teachers use lecture methods, question and answer, group discussions, and presentations of work results to create an active and meaningful learning atmosphere. The learning media used include textbooks, teaching modules, and simple visual aids that help students understand the relationships between ecosystem components. The main obstacles faced are limited audio-visual media and low reading interest among some students, but teachers try to overcome these through more varied and enjoyable learning activities. Overall, the implementation of CTL in science learning at SDN Gunggung 1 shows positive potential in improving students' conceptual understanding and learning motivation through real experiences that are relevant to everyday life.